Professional tennis is getting older: Age for the top 100 ranked tennis players - Gallo-Salazar, C.; Salinero, J. J.; Sanz, D.; Areces, F.; Del Coso, J. (International Journal of Performance Analysis in Sport, 2015)
The aim of this investigation was to determine age-related factors of the top 100 ranked men and women tennis players over the last few decades. The birth date and the ranking position of 1,040 top-100 tennis players (647 men and 393 women) were obtained from official public websites. The mean age of top 100 male tennis players increased significantly from 1984 to 2013 (24.6 ± 3.9 to 27.6 ± 3.2 yr; P P vs 22.8 ± 3.1 yr; P vs 24.8 ± 2.9 yr).